Moderacja - efektywna metodyka zarządzania współczesną organizacją - Łasiński, Gabriel; Głowicki, Piotr (Moderation - efficient methodic of knowledge management in contemporary organization, 2006)
The article describes moderation as a method (methodic) of group problem solving and Human Resources Management in contemporary organization. It includes definitions of cognize and practical problems. Moderation was defied as procedure group problem soling realized with important role of Moderator. Based on heuristic mechanism of problem solving, groups in work process are able to achieve synergy effect. Moderations are very useful in synergy process by exposing of group acclivity, responsibility for work effects, and partner relationship and consensus mechanism.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 639-646